A study on enhancing the role of clinical pharmacist in antimicrobial stewardship in Kerala vis a vis experiences from South Africa and United Kingdom - Dr Vrinda Nampoothiri; Dr Zubair Umer Mohamed; Dr Esmita Charani; Dr Sanjeev Singh (International Journal of Infectious Diseases)
Introduction: Whilst pharmacists are key stakeholders in Antimicrobial Stewardship (AMS), the degree of their participation varies in different countries. The current study aims to explore this variation and to develop context-specific interventions to enhance the role of clinical pharmacists in AMS in Kerala, India. Methods: A mixed method approach was adopted which included conducting a systematic review of literature on pharmacists-led or driven AMS interventions published between 01 January 2000 and 30 June 2020; semi-structured interviews of key AMS stakeholders (pharmacists and doctors) from India (Kerala), South Africa (Western Cape province) and the UK (England) to understand the reasons behind the variation in pharmacist roles in AMS in different income settings; a cross-sectional web-based survey among doctor of pharmacy students in Kerala to assess the level of training, education and the current practices in AMS; and semi-structured interviews among faculty and students to understand the potential impact of antimicrobial resistance (AMR) curriculum implemented in one of the pharmacy colleges in Kerala. Results: Whilst pharmacist-led or driven AMS interventions were reported only from high-income countries in the early 2000s, the systematic review (115 papers included) found a subsequent progressive increase in such studies from all income settings with a positive impact on patient care. The 38 interviews conducted in India, South Africa, and the UK revealed that the lack of exposure to AMS as part of pharmacy curricula and the support from hospital leadership shaped pharmacists’ roles in AMS. The survey conducted among 157 pharmacy students reported that despite training deficiency, the majority of the students review antimicrobial prescriptions as part of their clinical postings. Interviews among faculties (7) and students (6) showed that the implementation of the AMR curriculum was beneficial in introducing key concepts of AMR and AMS to pharmacy students which helped them during their clinical postings. Discussion: Through this iterative mixed-method analysis, context-specific interventions were developed to optimise pharmacist roles in AMS in Kerala, India: • pharmacy colleges- inclusion of AMR and AMS topics in pharmacy curricula, dedicated time for students to attend conferences, soft skill development for students • hospital administration- provide competent salary along with financial incentives and protected time for pharmacists to attend conferences/ seminars • doctors in AMS teams- provide training to pharmacists for patient case evaluation • pharmacists- proactively engage in AMS, collaborate with clinical teams, network with professionals from around the globe, initiate journal clubs for shared learning Conclusion: Increased opportunities for AMS training along with recognition of pharmacists' role in AMS can facilitate their participation in the programme, pushing back entrenched hierarchies and professional boundaries. This would be particularly beneficial in countries where the shortage of infectious disease physicians is a major impediment to AMS.